A rare case of bilateral bifid ribs: a case report - Patil, Vivek A.; Lal, Vikash; Shaikh, Tanveer P.; Narayan, Pranav; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
Bilateral bifid (bifurcation) rib is very rare malformation of thoracic wall. In this case, we observed variation involving right 6th and left 7th rib in 21 year female. The right 6th and 7th rib and its costal cartilage were bifurcated enclosing a small oval additional intercostal space.